Angabe:

Man löse die Differentialgleichungen!

y'' - 6y' + 9y = e^3x / x^2 (mittels Variation der Konstanten)

Lösung:

yh: L...Lamda

L^2 - 6L + 9 = 0
L1,2 = 3 +- Wurzel 9-9 => Doppellösung: L1,2 = 3

=> yh = x * c1 * e^3x + c2 * e^3x

Statt c1 und c2 => z1 und z2

yp = x * z1 * e^3x + z2 * e^3x
yp' = x * z1' * e^3x + z1 * (e^3x +3xe^3x) + z2' * ex^3x +3z2 * e^3x
Bedingung: x * z1' e^3x + z2' * e^3x = 0
yp'' = z1' * (e^3x + 3xe^3x) + z1 * (6e^3x + 9xe^3x) + 3z2' * e^3x + 9z2' * e^3x

Einsetzen:

z1' * (e^3x + 3xe^3x) + z1 * (6r^3x + 9xe^3x) + 3z2' * e^3x + 9z2 * e^3x - 6z1 * (e^3x + 3xe^3x) - 18z2 * e^3x + 9xz1 * e^3x + 9z2 * e^3x = e^3x / x^2

xz1' * e^3x = -z2' * e^3x => z2' = -xz1'

z1' * (e^3x + 3xe^3x) - 3xz1' = 1/x^2
z1' = 1/x^2 => z1 = -1/x

z2' = -xz1' => -x/x^2 => z2' = -1/x => z2 = ln|x|

=> y = yh + yp => y = xc1 * e^3x + c2 * e^3x - e^3x - ln|x|e^3x